2019
DOI: 10.1039/c9bm00052f
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple hydrogen bonds and thermo-triggered hydrophobic interactions generate dynamic hydrogels to modulate transplanted cell retention

Abstract: Supramolecular dynamic hydrogels with quadruple hydrogen bonds and thermo-triggered hydrophobic interactions demonstrate a promising capability of modulating transplanted cell retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…
The supramolecular polymer hydrogels feature self-healability, adjustable mechanical strength, and thermoplasticity, which are derived from the formation of supramolecular physical interactions in the hydrogel networks, such as H-bonding interactions, [6] host-guest interactions, [7] metal-ligand coordination interactions, [8] hydrophobic interactions, [9] multiple combined interactions. [10] Among them, H-bonds are generally weak noncovalent bonds, ubiquitous in biomolecules, but their synergistic interactions can reach a strength of the covalent bond; thus it is commonly utilized in designing supramolecular tough hydrogels. [11] Our previous study suggested that supramolecular polymer hydrogels based on single amide H-bonding interaction were unstable in water, [12] because the competitive solvation of H-bond donor and acceptor in polar solvents weakens its strengthening effect.
…”
mentioning
confidence: 99%
“…
The supramolecular polymer hydrogels feature self-healability, adjustable mechanical strength, and thermoplasticity, which are derived from the formation of supramolecular physical interactions in the hydrogel networks, such as H-bonding interactions, [6] host-guest interactions, [7] metal-ligand coordination interactions, [8] hydrophobic interactions, [9] multiple combined interactions. [10] Among them, H-bonds are generally weak noncovalent bonds, ubiquitous in biomolecules, but their synergistic interactions can reach a strength of the covalent bond; thus it is commonly utilized in designing supramolecular tough hydrogels. [11] Our previous study suggested that supramolecular polymer hydrogels based on single amide H-bonding interaction were unstable in water, [12] because the competitive solvation of H-bond donor and acceptor in polar solvents weakens its strengthening effect.
…”
mentioning
confidence: 99%
“…Gelatin methacryloyl (GelMA) and fluorescein isothiocyanate graft GelMA (GelMA-FITC) were synthesized according to the previous works. [20,32] CCk-8 kit was purchased from Tonkin institute of chemistry, Japan. Phosphate-buffered saline (PBS, pH = 7.4), Dulbecco's Modified Eagle's Medium (DMEM), fetal bovine serum (FBS), penicillin-streptomycin solution, live-dead staining solution were purchased from Life Technologies (Gibco, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The rheological tests of the hydrogels were determined according to our previously reported method. 37 2.2. Drug Release Assay.…”
Section: Methodsmentioning
confidence: 99%
“…The DOX& D PPA-1@HDU hydrogel was prepared similarly by further addition of DOX and the D PPA-1 peptide in the solution. The rheological tests of the hydrogels were determined according to our previously reported method …”
Section: Methodsmentioning
confidence: 99%